2022
DOI: 10.3389/fped.2022.877681
|View full text |Cite
|
Sign up to set email alerts
|

Small Airway Dysfunction Measured by Impulse Oscillometry and Fractional Exhaled Nitric Oxide Is Associated With Asthma Control in Children

Abstract: BackgroundImpulse oscillometry (IOS) and fractional exhaled nitric oxide (FeNO) are sensitive and non-invasive methods to measure airway resistance and inflammation, although there are limited population-based studies using IOS and FeNO to predict asthma control.ObjectiveThis study aimed to investigate the utility of IOS and FeNO for assessing childhood asthma control in terms of small airway dysfunction and airway inflammation.MethodsThis prospective observational cohort study enrolled 5,018 school children (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…34 Monitoring FENO levels can offer information on airway inflammation levels and help in treatment decisions. 35 We have shown a correlation between FENO levels and asthma control. 34,36 Elevated FENO levels observed during hospitalization were associated with pulmonary parenchymal involvement and cytokine storm in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…34 Monitoring FENO levels can offer information on airway inflammation levels and help in treatment decisions. 35 We have shown a correlation between FENO levels and asthma control. 34,36 Elevated FENO levels observed during hospitalization were associated with pulmonary parenchymal involvement and cytokine storm in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 70%
“…Using FENO assessment provides a convenient and non-invasive approach that could aid in monitoring parenchymal infiltration in these patients. 37 35,38 Due to strict lockdown policies and a lack of approval from public health authorities, it was not feasible to include post-COVID-19 asthmatic children with spirometry from the national survey. The clinical diagnosis of asthma with recurrent wheezing during the previous year was established according to the GINA criteria by a pediatric respiratory specialist.…”
Section: Introductionmentioning
confidence: 99%
“…This is useful in patients with alterations in thoracoabdominal compliance, obstructive pulmonary symptoms with normal spirometry, or in obese patients for whom it is not clear whether they have an obstructive or restrictive pulmonary pattern [ 69 , 70 ]. Previous studies have shown a strong correlation between an increase in resistance at 5 Hertz (Hz) minus 20 Hz (R5 − R20) in patients with small airway dysfunction and uncontrolled asthma [ 71 , 72 ]. In addition, the distal obstruction pattern can be identified by the R5 Hz value, which is higher than the upper limit of normality or greater than 1.64 standard deviations (SD) of the predicted value with normal R20 and AX values.…”
Section: Complementary Studies To Evaluate Lung Function In Patients ...mentioning
confidence: 99%
“…Observational studies have shown that the measurement of SAD through IOS parameters and FeNO can increase the accuracy of identifying uncontrolled asthma in pediatric patients [54,55]. In a study of 79 preschool children (ages 3-6 years), those with uncontrolled asthma had greater evidence of SAD, as measured by IOS parameters X5, AX, R5-R20, and FeNO levels, compared to children with controlled asthma [54]. The combination of IOS and FeNO improved the accuracy of the test in distinguishing controlled versus uncontrolled patients.…”
Section: Relationship Between Sad and Asthma Control In Childrenmentioning
confidence: 99%
“…The combination of IOS and FeNO improved the accuracy of the test in distinguishing controlled versus uncontrolled patients. The area under the curves in the receiver operating characteristic (ROC) analysis was 0.786 for FeNO alone, 0.751 for the IOS X5 parameter alone, and 0.866 for X5 combined with FeNO (cut-off value: 27 ppb) [54]. Similarly, in a large cohort of 560 school-age children (ages 6-12 years), the IOS parameter R5-R20 was the strongest predictor of uncontrolled asthma among lung function tests, including spirometry and FeNO [55].…”
Section: Relationship Between Sad and Asthma Control In Childrenmentioning
confidence: 99%